Membuat Pembelajaran Visual dengan Memanfaatkan Aplikasi Paint - Indah Nurzannah; Eigi Youlanda Dien; Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2023)
The purpose of the research in this article is to find out how early childhood activities improve visual intelligence skills through the application of paint at RA Al Muhajirin, Cimahi City and to find out how much the ability of visual intelligence increases through the application of paint. The formulation of the problem in this study is how the application of paint is carried out on the visual intelligence of early childhood at RA Al Muhajirin, Cimahi City. The research method used is the Classroom Action Research method. The subjects in this study were all early childhood, totaling 30 children. The instruments used are observation guidelines, interviews, and documentation. Data analysis technique uses descriptive qualitative. Data analysis uses the data reduction stage, data model, and drawing conclusions. The results showed an increase in the undeveloped category from 10 children (30%) to 1 child (3.6%), in the developing category from 14 children (49.9%) to 5 children (17.8%), in the category developing according to expectations as many as 3 children (12.3%) to 6 children (21.4%), and in the very well developed category as many as 3 children (9.7%) to 16 children (57.2%). It can be concluded that paint application can improve visual intelligence skills in early childhood at RA Al Muhajirin, Cimahi City.